2012
DOI: 10.1097/pai.0b013e3182240de1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Expression of ras p21 Oncoprotein and Mutation Status of the K-ras Gene in Sporadic Colorectal Cancer Patients in Tunisia

Abstract: Genetic K-ras alterations were rather low in the Tunisian population, but further study is necessary to unravel the molecular background of CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 21 publications
2
26
2
Order By: Relevance
“…The results showed that there was almost no p21Ras expression in normal colorectal mucosa, but high level expression of p21Ras in CRC and colorectal intraepithelial neoplasia. Together with the reported data (15,4346), we confirmed that p21Ras overexpression is an important event in colorectal carcinogenesis and plays a major role in the development of CRC.…”
Section: Discussionsupporting
confidence: 89%
“…The results showed that there was almost no p21Ras expression in normal colorectal mucosa, but high level expression of p21Ras in CRC and colorectal intraepithelial neoplasia. Together with the reported data (15,4346), we confirmed that p21Ras overexpression is an important event in colorectal carcinogenesis and plays a major role in the development of CRC.…”
Section: Discussionsupporting
confidence: 89%
“…K-ras is known as an oncogene (Izadi-Mood et al, 2013;Sammoud et al, 2012) which has been reported to be involved especially in lung cancer (Fatima and Yee, 2014;Rotella et al, 2014). Although lung cancer induced by radon has been confirmed by epidemiology studies (Choi and Mazzone, 2014;Melloni, 2014;Edwards et al, 2014), the role of K-ras gene in radon carcinogenesis is not yet identified.…”
Section: Discussionmentioning
confidence: 95%
“…Often, results were not statistically significant, possibly due to lack of power. Eighteen studies were included in an analysis on KRAS status in MC and NMC and KRAS mutations were found in MC more frequently (RR 1.27, 95% CI 1.14–1.41; Figure ) .…”
Section: Molecular Determinants In MCmentioning
confidence: 99%